A potential pitfall in studies of biological shape: Does size matter?. (6th September 2017) - Outomuro, David; Johansson, Frank
Abstract: The number of published studies using geometric morphometrics (GM) for analysing biological shape has increased steadily since the beginning of the 1990s, covering multiple research areas such as ecology, evolution, development, taxonomy and palaeontology. Unfortunately, we have observed that many published studies using GM do not evaluate the potential allometric effects of size on shape, which normally require consideration or assessment. This might lead to misinterpretations and flawed conclusions in certain cases, especially when size effects explain a large part of the shape variation. We assessed, for the first time and in a systematic manner, how often published studies that have applied GM consider the potential effects of allometry on shape. We reviewed the 300 most recent published papers that used GM for studying biological shape. We also estimated how much of the shape variation was explained by allometric effects in the reviewed papers. More than one‐third (38%) of the reviewed studies did not consider the allometric component of shape variation. In studies where the allometric component was taken into account, it was significant in 88% of the cases, explaining up to 87.3% of total shape variation. We believe that one reason that may cause the observed results is a misunderstanding of the process that superimposes landmark configurations, i.e. the Generalized Procrustes Analysis, which removes isometric effects of size on shape, but not allometric effects. Allometry can be a crucial component of shape variation. We urge authors to address, and report, size effects in studies of biological shape. However, we do not propose to always remove size effects, but rather to evaluate the research question with and without the allometric component of shape variation. This approach can certainly provide a thorough understanding of how much size contributes to the observed shaped variation. Abstract : The authors find that more than one‐third of the published studies using geometric morphometrics to study shape variation do not evaluate the allometric component of shape, which can explain more than 85% of the total shape variation.